Legal Consequences of Using Fake Halal Logos In The Food Industry - Vivi Sylvia Purborini (LPPM Universitas Bina Taruna Gorontalo, 2024)
This study aims to determine the legal consequences of counterfeiting halal logos on food products that have an important background from various perspectives, including law, economy, social, and ethics. Producers bear great responsibility in realizing halal products, so the responsibility of producers must be embodied in the production process itself by using halal ingredients accompanied by the installation of labels on the product packaging. This writing uses a normative method where in writing. The approach taken is the Conceptual Approach, starting from existing legal regulations and building a concept from views or doctrines that develop in Legal Science. Counterfeiting halal logos is a serious violation, both in terms of law and ethics. The sanctions imposed are not only intended to punish the perpetrators, but also to protect consumers and maintain market integrity. Law has an important role in regulating people's lives. For society, law is used as protection that can provide security and order in society. The halal certification and markings that have been carried out so far have only reached a small portion of food, beverage, drug, cosmetic, and other halal consumer products circulating in the community.